Hierarchy of Human Needs: A Humanistic Psychology Approach of Abraham Maslow - Ahmad Zainal Mustofa (Kawanua International Journal of Multicultural Studies, 2022)
This research describes the multilevel needs theory in Abraham Maslow's humanistic psychology. This research uses descriptive analytical method and is a literature review. Humanistic psychology is the third school in psychology after psychoanalysis as the first school and behaviorism as the second school. Unlike the previous second school, Abraham Maslow did not use people with neurotic symptoms and monkeys as objects of his observation. He made normal humans to observe personality which he later built into a theory of stratified needs. The stages in the hierarchy of needs theory are physiological needs, safety needs, belongingness needs, esteem needs and self-actualization needs. The result showed that humans have stages to reach the peak of existence which are interrelated with each other. If a stage has not been fulfilled, then he can not proceed to the next stage until the peak reaches the stage of self-actualization. This stage makes humans feel fully themselves while at the same time having fulfilled the basic needs in their lives.